(untitled) (Journal of Computational Mathematics, 2004)
The purpose of this paper is to construct a kind of multivariate NURBS surfaces by using the bivariate B-splines in the space S_2^1(Δ^(2)_mn) and discuss some properties of this kind of NURBS surfaces with multiple knots on the type-2 triangulation.